2021
DOI: 10.1007/s13595-021-01077-w
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, geographic, and climatic factors jointly shape leaf morphology of an alpine oak, Quercus aquifolioides Rehder & E.H. Wilson

Abstract: Key message Leaf symmetry and leaf size are explained by genetic variation between and within lineages and to a lesser extent by climatic factors, while leaf asymmetry can only be partly explained by geographic factors in Quercus aquifolioides Rehder & E.H. Wilson.Context Leaves are the primary photosynthetic organs of plants, and their morphology affects various crucial physiological processes potentially linked to fitness. Aims We explored the variation in leaf morphology of an alpine oak, Quercus aquifolioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 83 publications
1
13
0
Order By: Relevance
“…The allele sizes were subsequently scored using GeneMarker v. 2.2 (Softgenetics, United States), and the genotypes were checked visually two times. A subset of the data, 959 individuals from 58 study sites of Q. aquifolioides at 15 nSSRs, were from Du et al (2017) and Li Y. et al (2021) , and the additional data were first reported in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The allele sizes were subsequently scored using GeneMarker v. 2.2 (Softgenetics, United States), and the genotypes were checked visually two times. A subset of the data, 959 individuals from 58 study sites of Q. aquifolioides at 15 nSSRs, were from Du et al (2017) and Li Y. et al (2021) , and the additional data were first reported in this study.…”
Section: Methodsmentioning
confidence: 99%
“…To minimize the risk of clone selection, the populations were at least 10 km apart and all sampled individuals were located at least 5 m from each other [33]. From each individual, 10 fully developed leaves were collected at a height of 8-10 m around the crown of each tree [34], mainly under shaded conditions.…”
Section: Sampling and Landmark Configurationmentioning
confidence: 99%
“…The possible adaptive response of this variation to environmental conditions has been extensively investigated, perhaps more so than in any other plant genus (e.g. Zwieniecki et al ., 2004; Niinemets, 2015; Hipp et al ., 2018; Cavender‐Bares, 2019; Royer et al ., 2019; Li et al ., 2021; Sancho‐Knapik et al ., 2021; Skelton et al ., 2021). The oak genus is also a classic example for hybridization and introgression studies (Darwin, 1872; Rieseberg et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%